ANALISIS BAHAN KERAMIK PRIFILIT SEBAGAI PENGGANTI LOGAM PADA KETEL RICE COOKER - Agung Purnomo; Rizal Aditya Rifaii; Dian Puspita (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
This research aims (1) to determine the components of the rice cooker, (2) todetermine the distribution of heat in the rice cooker with aluminium pans and ceramicpans, (3) to determine the quality and taste of rice cooked by a rice cooker with analuminium pan and ceramic pan, (4) to determine the metal content of the rice cookerwith an aluminium pan and ceramic pan. The research is quantitative and qualitativein nature. The quantitative research is conducted by measuring the heat on the ricerice cooker with an aluminium pan and ceramic pan that can be made by theirphysical distribution system. The second is chemical metal content of rice cooker withan aluminium pan and ceramic pan. The qualitative research focuses on the qualityand flavor of rice with an organoleptic test. The result of this study is the product of arice cooker from ceramic pans from Pagar Jurang, Klaten. To support the physicalprocesses of the rice cooker, the study needs to detect the components in the ricecooker itself. Because the process of cooking rice by using a rice cooker cannot beseparated from the electronic system. The research continues on finding out thedifference in the cooking process by using ceramic pans and aluminium pans. Cookingrice within two hours has different detailed processes and different rice. The processuses a ceramic pan has increasing temperature which is longer than that using analuminum one. Basically, cooking uses a ceramic pan is successful but needs furtherresearch to produce good quality of rice faster. The results of the SSA test show thatceramic contains approximately 10% of aluminum that supports this behavior in theconductivity of the ceramic itself. If compared with the aluminum pan, aluminumwhich contains about 83% is certainly bigger than a ceramic pan and make a ricecooker with a ceramic pan environmentally friendlier than the aluminium pan. Basedon thenorganoleptic test, the rice cooked by using the ceramic pan is fresher and moredistinctive.